The effect of childbirth trauma on willingness to donate milk in women following perinatal loss: The mediating role of resilience - Fengling Li; Qi Shi; Tao Xiong; Yang Li; Yuxi Zheng; Guolu Jiang; Diana S. Duan; Xuemei Wei; Lijun Cui; Zhaoxia Chen (Wiley, 2024)
Abstract Limited studies have been conducted on Chinese women's willingness to donate milk following perinatal loss. In this study, we explore the relationship among childbirth trauma, willingness to donate milk, and resilience in women following perinatal loss, and the mediating effect of resilience between childbirth trauma and willingness to donate milk. A cross‐sectional study was carried out throughout 4 months. We used convenience sampling methods and recruited 241 women following a perinatal loss from eight tertiary hospitals in Sichuan Province, China. Participants completed four questionnaires during a face‐to‐face individual interview: the general information questionnaire, the Willingness to Donate Milk Scale (WMDS), the City Birth Trauma Scale, and the Brief Resilience Scale. SPSS 20.0 was used to analyze the collected data. In our study, childbirth trauma was negatively correlated with the total and each dimension score of WMDS (p < 0.001). Resilience was positively correlated with the total and each dimension score of WMDS (p < 0.001). Resilience partially mediated the relationship between childbirth‐related symptoms and willingness to donate milk (β = −0.38, 95% confidence interval [CI]: −0.50 to −0.26), which accounted for 69.03% of the total effect. Resilience partially mediated the relationship between general symptoms and willingness to donate milk (β = −0.31, 95% CI: −0.40 to −0.21), which accounted for 66.89% of the total effect. Resilience partially mediated the relationship between childbirth trauma and willingness to donate milk in women following perinatal loss. Our findings suggest that resilience can play a significant role in mediating the relationship between childbirth trauma and willingness to donate milk in women following perinatal loss. These results could help healthcare professionals design interventions for physical and mental recovery after perinatal loss.